Case Series and Systematic Review of Treatment Outcomes for Auricular Pseudocysts. Issue 5 (June 2021) - Ungar, Omer J.; Oron, Yahav; Cavel, Oren; Handzel, Ophir; Warshavsky, Anton; Horowitz, Gilad; Matot, Sofi
Abstract : Objective: Auricular pseudocyst (AP: intracartilaginous cyst, endochondral AP, cystic chondromalacia, and benign idiopathic cystic chondromalacia) is a benign condition of unknown etiology. This report systematically reviews the published demographics, treatment protocols, and outcomes of AP between the various medical disciplines, and compares the findings to a theretofore-unreported 12-patient cohort. Primary outcome measure was AP complete resolution without recurrence. Data Source: A systematic literature search of "MEDLINE" via "PubMed" and "Google Scholar" was performed in June, 2020. The 12 new patients were enrolled between January 2016 and December 2020. Study Selection: Seventy-four papers met the study inclusion criteria and provided data on sex distribution, surgical approach and outcome, performance of approaches according to medical specialty, and recurrence rates of the reported AP populations. Data Extraction: The appropriateness and study design quality were independently assessed by two reviewers. Data Synthesis: The primary outcome was therapeutic success. A comparative analysis was also performed on the same extracted information that was retrieved from the medical files of the 12 new patients (10 men, 2 women, average age 24 yrs, range, 17–38). Conclusions: AP is not uncommon. In line with the published literature, incision and curettage with excision of the anterior pseudocystic wall (deroofing) resulted in a recurrence rate of less than 17% with good cosmetic outcome among all 12 patients. Aspiration alone was associated with increased recurrence rates. Deroofing emerged as the preferred modality, with good cosmetic outcome and reduced recurrence rate. It was usually performed by otolaryngologists, while dermatologists used more conservative approach more frequently. Incision and drainage combined with compression reduces risk of recurrence.